2005
DOI: 10.1002/hyp.5553
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy computing based rainfall-runoff model for real time flood forecasting

Abstract: Abstract:This paper analyses the skills of fuzzy computing based rainfall-runoff model in real time flood forecasting. The potential of fuzzy computing has been demonstrated by developing a model for forecasting the river flow of Narmada basin in India. This work has demonstrated that fuzzy models can take advantage of their capability to simulate the unknown relationships between a set of relevant hydrological data such as rainfall and river flow. Many combinations of input variables were presented to the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(87 citation statements)
references
References 30 publications
0
80
0
3
Order By: Relevance
“…Most techniques, employed in this regard, have involved rainfall-runoff relationships that are in most cases based on linearity or piecewise linearity (Hsu et al, 1995). Others used rule-based systems that are governed by fuzzy inference rules (Nayak et al, 2005). This study makes a difference by testing a case sensitive approach of the variables (rainfall-discharge) in the basin, exploring various fits and suggesting fits best suited for rainfall-discharge correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Most techniques, employed in this regard, have involved rainfall-runoff relationships that are in most cases based on linearity or piecewise linearity (Hsu et al, 1995). Others used rule-based systems that are governed by fuzzy inference rules (Nayak et al, 2005). This study makes a difference by testing a case sensitive approach of the variables (rainfall-discharge) in the basin, exploring various fits and suggesting fits best suited for rainfall-discharge correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Chang and Chen (2001) proposed a counter-propagation fuzzy-neural network capable of automatically generating rules for use in clustering input data to enable streamflow prediction. Nayak et al (2005) employed fuzzy computation in the development of a realtime flood forecasting model. They concluded that the recursive use of a one-step-ahead forecast model to predict flow using longer lead times produces results better than those achieved using independent fuzzy models for the forecasting of flow under various lead times.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, black-box modeling does not require a deep knowledge of the underlying physics and also can solve the problem of the scarcity of the data. Several black-box models have been developed and used in hydrological forecasting, such as fuzzy theory [2,3], artificial neural network [4,5], chaos [6], genetic programming [7], support vector machine [8], and so on.…”
Section: Introductionmentioning
confidence: 99%